The Design and Development of Community Textile Products from Banana Fiber Blends as Commercial Prototypes - Inpakdee, Chintana; Soodsang, Nirat (Community and Social Development Journal, 2025)
This research is predicated on the imperative to enhance the economic value of indigenous materials, specifically banana fiber, through the integration and development of community-based textile products with potential for commercial scalability. The objective of this research was to develop community textile products from banana fiber blends as commercial prototypes. The creation was divided into two parts: the creation of textile designs and the development of textile product prototypes from the needs of 400 working-age consumers aged between 25 and 45 years. The findings revealed that the yarn blend with banana fiber using a blend ratio of cotton, banana fiber, and Eri silk (70:20:10), spun in OE Spinning, yarn size 10/1, when used to create woven fabric patterns using the Kite technique resulted in new designs inspired by parts of a banana tree, which included designs based on banana blossom tops, banana fibrous layers, and banana blossoms. These developed designs could be applied to create textile fabrics with other techniques at the community level. When the developed textile was made into 10 daily wearable prototypes, the acceptance of the products by the consumers was at a good level. The overall mean acceptance score of 4.70, which was higher than the predetermined criterion of 4.00. Therefore, developing a prototype community textile product from banana fiber blend to commercial scale is the new body of knowledge that the community can use, develop, and expand its textile product in the future.